Formation of a complete stress-strain curve of concrete using digital image corellation - Blikharskyy, Yaroslav; Pavliv, Andrii (Eastern-European Journal of Enterprise Technologies, 2021)
This paper reports the development and verification of a new procedure for formation of a complete stress-strain curve of concrete with a downward region of strain by using a digital image correlation method. A new technique to build spectle patterns on the surface of concrete is described. That makes it possible to accurately enough reproduce the spectle patterns on the surface of concrete and perform a high-quality analysis of strains involving digital image correlation. The advantages of this research technique have been established when predicting the formation of internal cracks in concrete followed by their propagation. In addition, using the digital image correlation methodology makes it possible to obtain strains of the entire studied plane of the sample at each stage of loading. This procedure provides an opportunity to investigate a change in strains and the movement of individual points or areas when studying concrete surfaces. That is a relevant issue as it enables more detailed diagnostics of existing reinforced concrete structures. To check the accuracy of this procedure application, a mechanical gauge with an accuracy of 0.001 mm was additionally installed. 2 high-speed monochrome CCD cameras with different lenses were used in determining concrete strains involving the digital image correlation technique. The deformations were controlled with a period of time every 250 ms. The load was controlled by an additional third camera with a speed of 50 frames/second. The result of the experimental study is the formed full concrete destruction diagram with a downward region of strain. The deviation of the results of strains based on the mechanical gauge with an accuracy of 0.001 mm with a base of 200 mm from those acquired by the digital image correlation procedure was mainly up to 10 %, which confirms the reliability of the results. The results of this work allow a more accurate calculation of reinforced concrete structures in the practice of design, inspection, or reinforcement of existing structures